The epithelium takes the stage in asthma and inflammatory bowel diseases - López-Posadas, Rocío; Bagley, Dustin C.; Pardo-Pastor, Carlos; Ortiz-Zapater, Elena (Frontiers in Cell and Developmental Biology, 2024)
The epithelium is a dynamic barrier and the damage to this epithelial layer governs a variety of complex mechanisms involving not only epithelial cells but all resident tissue constituents, including immune and stroma cells. Traditionally, diseases characterized by a damaged epithelium have been considered “immunological diseases,” and research efforts aimed at preventing and treating these diseases have primarily focused on immuno-centric therapeutic strategies, that often fail to halt or reverse the natural progression of the disease. In this review, we intend to focus on specific mechanisms driven by the epithelium that ensure barrier function. We will bring asthma and Inflammatory Bowel Diseases into the spotlight, as we believe that these two diseases serve as pertinent examples of epithelium derived pathologies. Finally, we will argue how targeting the epithelium is emerging as a novel therapeutic strategy that holds promise for addressing these chronic diseases.